Does the subtype of acute coronary syndrome treated by percutaneous coronary intervention predict long-term clinical outcomes? - Biswas, S.; Andrianopoulos, N.; Papapostolou, S.; Noaman, S.; Duffy, S.; Lefkovits, J.; Brennan, Angela; Walton, A.; Shaw, J.; Ajani, A.; Clark, D.; Freeman, M.; et al. (2018)
© The Author 2017. Aims The prognosis of patients undergoing percutaneous coronary intervention (PCI) for different subtypes of acute coronary syndromes (ACS) remains unclear. We compared short- and long-term mortality in patients undergoing PCI for unstable angina (UA), non-ST-elevation myocardial infarction (NSTEMI), and ST-elevation myocardial infarction (STEMI). Methods and results This was a retrospective cohort study of 13 184 patients (5966 STEMI, 5307 NSTEMI, and 1911 UA) undergoing PCI between 1 January 2005 and 30 November 2013 in a multi-centre registry. Clinical and procedural characteristics, as well as outcomes, were compared by ACS subtype. Long-term all-cause mortality data were obtained via linkage to the National Death Index (NDI). Patients with STEMI compared with NSTEMI and UA were younger (62.9 ± 12.8 vs. 64.7 ± 12.5 vs. 65.5 ± 11.8 years; P < 0.01), had fewer comorbidities including diabetes, heart failure, and previous myocardial infarction (all P < 0.01). Procedural success was similar across all groups (P = 0.54). In-hospital, 30-day and 1-year all-cause mortality increased significantly from UA to NSTEMI to STEMI patients (1-year mortality 2.5% vs. 4.5% vs. 8.7%; P < 0.01). Kaplan-Meier survival estimates showed increased early mortality in the STEMI group (log-rank P < 0.01). However, after approximately 8.2 years, survival was similar across all groups. In a proportional-odds model using flexible parametric survival modelling, ACS subtype was not an independent predictor of NDI-linked mortality [UA: odds ratio (OR) 0.85, 95% CI 0.71-1.02; STEMI: OR 1.01, 95% confidence interval (CI) 0.88-1.16; NSTEMI as reference category]. Conclusion Despite disparate baseline characteristics and differences in short-term mortality, long-term mortality was similar across the spectrum of ACS treated by PCI and contemporary medical therapy.